2010
DOI: 10.1177/039463201002300315
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide fromPorphyromonas GingivalisStimulates Rat Mast Cells to Cysteinyl Leukotriene Generation and Upregulates Toll-like Receptor −2 and −4 Expression

Abstract: Mast cells are found in all tissues of the oral cavity and it is suggested that they take part in the development of oral inflammation. As Porhyromonas gingivalis is widely recognized as a major pathogen in the development and progression of gingivitis and periodontitis, the aim of our study is to determine the effect of P. gingivalis lipopolysaccharide (LPS) on mast cell degranulation, cysteinyl leukotriene (cysLT) generation, and migration, as well as Toll-like receptor (TLR)-2 and -4 expression. Experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…To determine the specificity of PgLPS 1690 for HDPs, we tested its effect on Ca 2ϩ mobilization induced by C3a. While PgLPS 1690 inhibited Ca 2ϩ responses to HDPs, it had no effect on the response to C3a ( Mast cells express TLR2 and TLR4, key receptors for LPS recognition, yet previous studies have shown that PgLPS does not induce degranulation in rat peritoneal mast cells (55). Similarly, we found that PgLPS 1690 and PgLPS 1435/1449 did not cause degranulation in human LAD2 cells ( Fig.…”
Section: Resultssupporting
confidence: 49%
“…To determine the specificity of PgLPS 1690 for HDPs, we tested its effect on Ca 2ϩ mobilization induced by C3a. While PgLPS 1690 inhibited Ca 2ϩ responses to HDPs, it had no effect on the response to C3a ( Mast cells express TLR2 and TLR4, key receptors for LPS recognition, yet previous studies have shown that PgLPS does not induce degranulation in rat peritoneal mast cells (55). Similarly, we found that PgLPS 1690 and PgLPS 1435/1449 did not cause degranulation in human LAD2 cells ( Fig.…”
Section: Resultssupporting
confidence: 49%
“…It is also known that in response to treatment with lipoteichoic acid, LPS, poly(I:C) and flagellin induce expression of IL-8 by coupling with the respective receptors TLR 2, 3, 4 and 5 [32,33]. Likewise, it has been demonstrated that purified preparations of LPS obtained from P. gingivalis stimulate receptors TLR 2 and TLR4 [34]. The effect on expression of these receptors is of great importance, since the pathogen-associated molecular patterns present in dental plaque participate in inducing expression of inflammatory cytokines [35].…”
Section: Discussionmentioning
confidence: 98%
“…Only TLR2, TLR3, and TLR4 proteins were found in mast cells from isolated human nasal polyps [22], murine peritoneal cavity [38], and FSMC [30]. Our previous studies have shown that freshly isolated rat peritoneal mast cells express both surface TLR2 and TLR4 molecules [20, 39], as well as TLR3 and TLR7 surface proteins [40, 41]. In this study we evaluated the expression of TLR receptors in native fully mature rat mast cells freshly isolated from the peritoneal cavity, that is connective tissue type mast cells.…”
Section: Discussionmentioning
confidence: 99%